A Boy With KIF11-Associated Disorder Along With ADHD and ASD: Collaboration Between Paediatrics and Child Psychiatry - Annelien Marcelis; Evelyne Van Reet (Case Reports in Psychiatry)
Kinesin family member 11 (KIF11)-associated disorder, a rare condition caused by autosomal dominant mutations in the KIF11 gene, presents with microcephaly, chorioretinal dysplasia, lymphoedema, and varying degrees of intellectual disability. While intellectual disability is often described in the literature on KIF11 mutations, autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) are only mentioned by a few authors but not thoroughly investigated. We present a case report of an 8-year-old boy with KIF11-associated disorder alongside ADHD and ASD but without intellectual disability. Genetic testing confirmed a KIF11 mutation. Cognitive, language, and motor assessments revealed delays in fine motor skills and attention deficits. The diagnosis of ADHD was confirmed by a child neurologist through multidisciplinary investigations, while the ASD diagnosis was established by a child psychiatrist. Despite the challenges of delayed psychiatric assessment, interventions including physiotherapy and medication management were initiated with positive results. We designed a parent support group survey that showed a higher prevalence of neurodevelopmental disorders in children with KIF11 mutations compared to the general population. Therefore, low-threshold referrals to a child psychiatrist have to be made when the potential presence of developmental problems is suspected. Collaboration between ophthalmologists, paediatricians, and child psychiatrists is crucial for early detection and intervention. Addressing developmental disorders promptly improves long-term outcomes and enhances quality of life. Moreover, gaining a deeper understanding of the higher prevalence of ASD and ADHD in individuals with KIF11 mutations could offer valuable insights into the genetic mechanisms underlying neurodevelopmental disorders.